Gendering security and insecurity post/neocolonial security logics and feminist interventions - Purewal, Navtej Kaur; Dingli, Sophia (Thirdworlds, 2019)
This volume contributes to debates which seek to move feminist scholarship away from the reification of the war/peace and security/economy divides. By gendering (in)securities in 'states of exception' and other paradigms of government related to it, especially in postcolonial and neocolonial contexts, the book provides an approach that allows us to study the complex and interrelated security logics, which constitute the messy realities of different - and particularly vulnerable - subjects' lives